Repairing customer trust after a product-harm crisis with high crisis responsibility. Case: Musti ja Mirri - Korpilaakso, Markus (2025)
Product-harm crises have been on the rise for the last couple of decades due to factors including increased consumer demands and more intricate manufacturing processes. At worst, product-harm crises can threaten the existence of business and pose serious harm to consumers. Navigating such crises and repairing damaged customer trust requires good crisis management know-how and carefully selected crisis communication strategies. This master’s thesis examines how customer trust can be repaired during and after a product-harm crisis that has involved a high crisis responsibility. While the study mainly focuses on the role of crisis communication in customer trust repair, the impact of operational actions on trust repair is also considered. The literature review consists of relevant theories that outline various tactics for responding to a crisis, minimizing reputational damage, and repairing trust in the long term. These include trust repair mechanisms, situational crisis communication theory (SCCT), image repair theory (IRT), and discourse of renewal (DOR). The study follows a qualitative research approach and relies on semi-structured interviews as the primary data. The interviews were conducted using purposive sampling, which recognized participants with similar characteristics relevant to the research topic. In this case, the common characteristic was extensive work experience in either crisis management or crisis communication, or both. The case study of Musti ja Mirri’s dog food crisis from 2023 was used in the interview to provide real-life context for the research topic. The interview data was analyzed by utilizing thematic analysis, which enabled the identification of patterns in the responses. The results of this study contribute to prior research supporting the idea that accommodative crisis response strategies are beneficial for trust repair when high crisis responsibility is involved. The insights highlight the importance of various factors in customer trust repair, such as accountability and crisis communication that relies on transparency and empathy. Additionally, corrective actions, the organization’s authenticity, and organizational learning are important in trust repair.